The Effectiveness of Istighfar Dzikr Therapy in Increasing Domestic Violence Victims’ Resilience - Trya Dara Ruidahasi; Fuad Nashori (Universitas Muhammadiyah Yogyakarta, 2021)
Resilience encourages individuals to face, overcome, and become stronger in difficult situations, especially for wives of domestic violence victims to face their issues. This study aims to observe the effectiveness of istighfar dzikr therapy in increasing the resilience of the wives. This study used a mixed-method with sequential explanatory design. The first stage was a quantitative approach involving 12 wives as victims of domestic violence in Yogyakarta. The second stage was a qualitative approach to deepen the quantitative data. The participants were divided into the control group (n=6) and the treatment group (n=6). They were selected using a purposive sampling technique, and the data were collected by CD-RISC (Connor-Davidson Resilience Scale). This study applied a nonrandomized control group with a pre-test-post-test design. The data analysis technique quantitatively used the SPSS software version 25. Then, Anava Mixed Design was used to analyze. The results showed an increase in resilience scores in the treatment group, and the treatment group had higher resilience scores than the control group. Participants in the treatment group were able to maintain the therapeutic effect two weeks after the istighfar dzikr therapy.